Analysis of Hugo Famous Trademark Dispute from the Perspective of Legal Protection in Indonesia - Rusdinah, Rusdinah; Sitorus, Rolib (PT FORMOSA CENDEKIA GLOBAL, 2025)
Hugo, one of the trademarks under Hugo Boss, is often the target of violations in the form of registering trademarks that are essentially similar to the Directorate General of Intellectual Property Rights, which is considered unfair business competition, because it can harm the owner of the original trademark, mislead consumers, and damage the reputation of the brand that has been built. This study examines the analysis of the famous Hugo trademark dispute from the perspective of legal protection in Indonesia, which is the object of the dispute in decision Number 10 PK / Pdt.Sus-HKI / 2023.The focus of the research is an analysis of the legal basis underlying the protection of famous trademarks in Indonesia and a review of legal considerations by the panel of judges in the trial process in 3 (three) stages, namely the first decision, cassation, and judicial review. The research method used in this study is the normative legal research method by examining court decisions and laws and regulations as primary legal materials. Books, documents, journals, and scientific works as secondary legal materials. As well as official and trusted publications as tertiary legal materials. The analysis technique applied in this study is a qualitative method through literature studies. The results of the research and analysis obtained are that the Plaintiff as the owner of the HUGO BOSS brand is the first registrant and user of the HUGO BOSS brand and variations of HUGO and/or BOSS based on the first to file system, so that the Plaintiff is the legal owner of the HUGO BOSS brand and is also a well-known brand according to the evidence of its registration in various countries. The registration of the HUGO brand owned by the Defendant is considered to be in bad faith because its brand is essentially similar to the Plaintiff's brand.